Numerical modelling of the cluster targets for their optimization in femtosecond-laser-cluster-driven experiments. (21st June 2017) - Boldarev, A.S.; Faenov, A.Y.; Fukuda, Y.; Jinno, S.; Pikuz, T.A.; Kando, M.; Kondo, K.; Kodama, R.
Abstract: The interaction of femtosecond ultra-intense laser pulses with clusters increases absorption of the incident laser light compared with the interaction with solid targets and leads to enhanced generation of different quantum beams with unique parameters. Future investigations of such interaction urgently need detailed modeling and optimization of cluster parameters, for instance, in order to obtain the clusters with desired size, or some specific spatial configuration of the target etc. A numerical model of gas-cluster targets production by the nozzle flows of gases and binary mixtures is presented. Some previous results of the model utilization are summarized, and some new results are given. Techniques of experimental verification of the numerical results are discussed.